2011
DOI: 10.3382/ps.2010-00727
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of corn distillers dried grains with solubles as an alternative ingredient for broilers

Abstract: The effects of graded levels of corn distillers dried grains with solubles (DDGS) were investigated as a partial replacement for sources of protein, energy, and other nutrients for broilers when the digestible amino acid balance was maintained. Zero, 8, 16, and 24% DDGS were incorporated into isonutritive diets at the expense of corn, soybean meal, and dl-Met. Poultry oil, l-Lys, and l-Thr additions increased with increasing levels of DDGS. Diets were each fed to 36 Cobb 500 straight-run broilers in 6 floor pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 12 publications
5
26
0
Order By: Relevance
“…Signifi cant diff erence was found between C and D18 groups (P < 0.05), but this trend was not confi rmed in the second experiment. Similar results published Shim et al (2011). But they found signifi cantly higher proportion of abdominal fat in male broilers already at feeding 60 g/kg of DDGS.…”
Section: Carcass Characteristicssupporting
confidence: 79%
See 1 more Smart Citation
“…Signifi cant diff erence was found between C and D18 groups (P < 0.05), but this trend was not confi rmed in the second experiment. Similar results published Shim et al (2011). But they found signifi cantly higher proportion of abdominal fat in male broilers already at feeding 60 g/kg of DDGS.…”
Section: Carcass Characteristicssupporting
confidence: 79%
“…The main reason for mortality was SDS. Shim et al (2011) also published higher growth of chickens fed higher amount of DDGS (≥ 8%), till 18 th day of age but at 42 nd day of age there was not any diff erence among the groups. Wang et al (2007a) also did not fi nd signifi cant eff ect of higher levels of DDGS in the diets for broilers on their performance, only at including 25% of DDGS they observed higher feed consumption and consequently higher feed conversion ratio in comparison with chickens fed diets without DDGS.…”
Section: Growth Performancementioning
confidence: 99%
“…There was no significant difference between DDGS sources either (p>0.05). Similare results have been reported elsewhere (Guney et al, 2013) when broilers were fed low-oil DDGS for 18 d. Feeding levels as high as 15% of conventional DDGS (10% fat) did not significantly affect growth performance (Cortés et al, 2012;Lumpkins et al, 2004;Shim et al, 2011). Levels higher than 15%, however, significantly reduced growth performance rate.…”
Section: Effect Of Feeding Low-oil Ddgs To Laying Hens and Broiler Chsupporting
confidence: 77%
“…In contrast, Shim et al (2011) reported that female broilers accumulated more abdominal fat than males.…”
Section: Effect Of Feeding Low-oil Ddgs To Laying Hens and Broiler Chmentioning
confidence: 80%
“…In addition, the high demand for corn, wheat and soybean for human consumption and biofuel production has led to a surge in their prices worldwide (Ojewola et al, 2004), consequently increasing feed cost. Alternative cereals like barley, rye and sorghum can replace corn and wheat as energy sources, whereas oil meals from cottonseed and sunflower seed, and industrial co-products such as dried distillers grains with solubles and brewers dried grains can replace soybean meal as protein sources in poultry feed (García et al, 2008;Shim et al, 2011).…”
Section: Introductionmentioning
confidence: 99%